1993
DOI: 10.1302/0301-620x.75b1.8421011
|View full text |Cite
|
Sign up to set email alerts
|

The relative strengths of the rotator cuff muscles. A cadaver study

Abstract: We studied five cadaver shoulders to determine the strength relationship of the four rotator cuff muscles. The mean fibre length and volume of each muscle were measured, from which the physiological cross-sectional area was calculated. This value was used to estimate the force which each muscle was capable of generating. The lever arm of each muscle about the humeral head was then measured and the moment exerted was calculated. The strength ratios between the muscles were more or less constant in the five spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(96 citation statements)
references
References 0 publications
2
82
0
2
Order By: Relevance
“…Several studies have pointed out that some muscles-for instance, the deltoid muscle (Michiels and Bodem 1992), the trapezius muscle (Inman et al 1944, Jensen 1995, and the subscapularis muscle (Kadaba et al 1992)-should be regarded not as single muscles but rather as functional units which work on their own to a large extent. Recent studies have shown a complex interaction between the shoulder muscles in shoulder joint movements (Pearl et al 1992, Keating et al 1993. Not only the supraspinatus muscle but also the rest of the rotator cuff muscles contribute significantly to abduction (Sharkey et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have pointed out that some muscles-for instance, the deltoid muscle (Michiels and Bodem 1992), the trapezius muscle (Inman et al 1944, Jensen 1995, and the subscapularis muscle (Kadaba et al 1992)-should be regarded not as single muscles but rather as functional units which work on their own to a large extent. Recent studies have shown a complex interaction between the shoulder muscles in shoulder joint movements (Pearl et al 1992, Keating et al 1993. Not only the supraspinatus muscle but also the rest of the rotator cuff muscles contribute significantly to abduction (Sharkey et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of the subscapularis tendon in shoulder function, which has been exemplified in several studies, 10,[18][19][20] the need to properly recognize and treat subscapularis tendon tears cannot be underscored. The subscapularis, being the largest and most powerful of the rotator cuff muscles, alone provides approximately 50% of the rotator cuff force, 21) and is important for arm elevation. 20) Intriguingly, the subscapularis muscle has been shown to be more active in patients with asymptomatic cuff tears implying that the subscapularis tendon may play a compensatory role during posterosuperior cuff tears.…”
Section: Discussionmentioning
confidence: 99%
“…견갑하근 (subscapularis muscle)은 회전근 개 (rotator cuff) 중 가장 크고 강력한 근육으로, 1) 견관 절의 내회전, 외전 기능 및 수동적, 능동적 안정화 구 조물로 작용한다. [2][3][4][5][6][7][8][9] 또한 회전근 개의 주요 근육들 중 하나로서, 'force couple' 의 개념으로 견관절이 정상적 이며 조절된 운동을 하는데 중요한 기능을 하고 있다.…”
Section: 서 론unclassified